Different b-adrenoceptor subtypes coupling to cAMP or NO/cGMP pathways : implications in the relaxant response of rat conductance and resistance vessels (2013)
ABSTRACT: To analyse the relative contribution of b1-, b2- and b3-adrenoceptors (Adrb) to vasodilatation in conductance and resistance vessels, assessing the role of cAMP and/or NO/cGMP signalling pathways. Experimental Approach Rat mesenteric resistance artery (MRA) and aorta were used to analyse the Adrb expression by real-time-PCR and immunohistochemistry, and for the pharmacological characterization of Adrb-mediated activity by wire myography and tissue nucleotide accumulation. Key Results The mRNAs and protein for all Adrb were identified in endothelium and/or smooth muscle cells (SMCs) in both vessels. In MRA, Adrb1 signalled through cAMP, Adrb3 through both cAMP and cGMP, but Adrb2, did not activate nucleotide formation; isoprenaline relaxation was inhibited by propranolol (β1, β2), CGP20712A (β1), and SQ22536 (adenylyl cyclase inhibitor), but not by ICI118,551 (β2), SR59230A (β3), ODQ (soluble guanylyl cyclase inhibitor), L-NAME or endothelium removal. In aorta, Adrb1 signalled through cAMP, while β2- and β3-subtypes through cGMP; isoprenaline relaxation was inhibited by propranolol, ICI118,551, ODQ, L-NAME, and to a lesser extent, by endothelium removal. CL316243 (β3-agonist) relaxed aorta, but not MRA. Conclusion and Implication Despite all three Adrb subtypes being found in both vessels, Adrb1, located in SMCs and acting through the adenylyl cyclase/cAMP pathway, are primarily responsible for vasodilatation in MRA. However, Adrb-mediated vasodilatation in aorta is driven by endothelial Adrb2 and Adrb3, but also by the Adrb2 present in SMCs, and is coupled to the NO/cGMP pathway. These results could help to understand the different physiological roles played by Adrb signalling in regulating conductance and resistance vessels.